Monetary and Financial Thinking in Europe: Evidence from Four Decades of SUERF - Jean-Paul Abraham (SUERF - The European Money and Finance Forum, 2003)
2003 marks the 40th anniversary of the founding of SUERF. To mark this milestone, some time ago the Council of Management commissioned Professor Jean-Paul Abraham to write a commemorative report. His mandate was not to write a history of SUERF itself (that would be too self-indulgent) but to write a reflective review of European monetary arrangements and related issues as seen through the various activities (mainly Colloquia) of SUERF. A total of twenty three Colloquia volumes have been published to date on various aspects of European monetary and financial arrangements, banking and financial markets, globalisation and its implications, corporate governance, alternative financial structures of national financial systems, and monetary policy to mention but a few. Jean-Paul is eminently qualified to undertake this task and we are extremely grateful to him for taking on this herculean venture. Professor Abraham is a distinguished academic and has been a professional banker in his long and distinguished career. Jean-Paul is also a distinguished past President of SUERF (1994-1997). We judged that his perspectives, and his intimate knowledge and experience of SUERF and its activities, would be both interesting and valuable. SUERF Colloquia have been held in sixteen countries and have had a varied mix of speakers from central banks, the financial sector and academics. Over the last forty years there have, of course, been enormous changes in European and international monetary and financial arrangements, and the role of private markets and institutions. The report brings this out very well. What is particularly interesting in the report is how, almost irrespective of the topic of the Colloquium, certain common issues seem to emerge. Looking back, some of the 431 papers published in the SUERF Colloquium volumes have been very prescient and by people who have shaped events. Professor Abraham's report has been published to coincide with the SUERF seminar which was held at, and hosted by, the Banque de France in Paris on October 24th, 2003.
Keywords: E42; E44; E52; E58; F33; F34; F36; G10; G20; G21; N14; N24; 330; Economic History; Monetary Policy; Financial Stability; Central Banking; International Monetary System; International Monetary Arrangements; European Monetary Integration; Financial Institutions and Services; Geldpolitik; Währungssystem; Wechselkurspolitik; Wirtschaftsforschung; Europa